EXPERIMENTAL STUDY OF MAGNETIC FLUID SEAL - V. G. Bashtovoi; A. M. Algadal; V. B. Samoilov (Наука и техника)
Dependences of critical pressure drop, being held by magnetic fluid seal, on time in a static state and shaft rotation velocity in dynamics have been experimentally determined. The significant influence of particles’ redistribution in magnetic fluid on static parameters of magnetic fluid seal has been established.